Two-Photon Absorption in Pentacene Dimers: The Importance of the Spacer Using Upconversion as an Indirect Route to Singlet Fission - Garoni, Eleonora; Zirzlmeier, Johannes; Basel, Bettina; Hetzer, Constantin; Kamada, Kenji; Guldi, Dirk Michael; Tykwinski, Rik (Journal of the American Chemical Society, 2017)
In this proof of concept study, we show that intramolecular singlet fission (iSF) can be initiated from a singlet excited state accessed by two-photon absorption, rather than through a traditional route of direct one-photon excitation (OPE). Thus, iSF in pentacene dimers 2 and 3 is enabled through NIR irradiation at 775 nm, a wavelength where neither dimer exhibits linear absorption of light. The adamantyl and meta-phenylene spacers 2 and 3, respectively, are designed to feature superimposable geometries, which establishes that the electronic coupling between the two pentacenes is the significant structural feature that dictates iSF efficiency.
CRIS-Team Scopus Importer:2022-04-14